Correlation of diagnostic accuracy of computed tomography with magnetic resonance imaging in local staging of carcinoma rectum at tertiary care center - Danish, Mozaffar; Bhat, Shreya; Sharma, Sachin; Ahmad, M. Shamim (International Journal of Research in Medical Sciences, 2024)
Background: Rectal cancer is third most common cancer related death worldwide. Cross sectional imaging techniques like computed tomography (CT) and magnetic resonance imaging (MRI) play a major role in preoperative staging. En-bloc resection of mesorectum and preoperative neoadjuvant chemoradiotherapy has significant role to reduce postsurgical recurrence. Methods: A cross-sectional observational study was conducted in the department of radiology, Narayan medical college and hospital Sasaram over a period of 12 months from August 2022 to September 2023. A total of 40 patients with biopsy proved rectal carcinoma were included, Local staging of carcinoma rectum was performed using MRI pelvis, MDCT abdomen and pelvis, the results were analysed and correlated. Results: The current study is aimed to correlate the diagnostic accuracy of CT with MRI in local staging of carcinoma rectum. Rectal cancer was more common in elderly mostly above 50 years of age. 65% of the cases showed irregular circumferential wall thickening and 35% showed polypoidal growth. On correlating with MRI, CT showed an overall good sensitivity, specificity, and accuracy in diagnosing tumor staging, mesorectal fascia (MRF) involvement and extramural vascular invasion (EMVI). CT can be considered as a reliable imaging modality for local staging of rectal cancer. Conclusions: MRI and MDCT both are complementary imaging modalities in preoperative staging of rectal cancer. MRI is the best available imaging modality for the local staging of patients and has the potential to play an important role in accurately differentiating which patients should receive preoperative chemoradiation prior to total mesorectal excision. CT can be considered as a reliable imaging modality for assessing local staging of rectal cancer.